Profile description of Pancasila students in fiction in the thematic book for grade 3: loving plants and animals’ chapter - Siti Nurhayati; Fachri Helmanto (LADU: Journal of Languages and Education, 2021)
Background: Fiction text is one of the genres of literary works containing fictional story elements created by the author’s imagination. Fiction is believed to be a reading that adds knowledge, insight, enlightens the soul of the reader, and as an effort to instill values, especially the value of educational character to students. Purpose: This study aims to determine the value of educational characters in fiction stories. Design and methods: This research was conducted using a qualitative approach to content analysis methods or content analysis with descriptive analysis techniques. The source of the data used is the document in the form of a grade 3 thematic book on the chapter of loving plants and animals. Results: The results of the study revealed that in the text of fiction in the thematic book grade 3 theme 2 elementary school there are character values ​​of faith, fear of God Almighty with elements of personal morals, and character values ​​of mutual cooperation with elements of caring and sharing. Meanwhile, the character values ​​that have not yet emerged are global diversity, independence, critical reasoning, and creativity.